The Role of Mindful Parenting in Individual and Social Decision-Making in Children - Wong, Kristyn; Hicks, Laurel M.; Seuntjens, Terri G.; Trentacosta, Christopher J.; Hendriksen, Tessel H. G.; Zeelenberg, Marcel; van den Heuvel, Marion I. (Frontiers in Psychology, 2019)
Children are confronted with an increasing amount of choices every day, which can be stressful. Decision-making skills may be one of the most important “21st century skills” that children need to master to ensure success. Many aspects of decision-making, such as emotion regulation during stressful situations, develop in the context of caregiver-child interactions. This study examined whether mindful parenting predicts children’s individual and social decision-making. The current study included 63 mother-child dyads from The Netherlands (Child Mage = 5.11, SD = 0.88, 50.8% girls). Mothers completed the Dutch version of the Interpersonal Mindfulness in Parenting Scale (IM-P). A “Choice Task” was developed to measure individual decision-making skills, and a “Sharing Task” was created to measure social decision-making in young children. Higher maternal mindful parenting significantly predicted more sharing after controlling for covariates (child age, sex, SES, maternal education level; Wald = 4.505, p = .034). No main effect of maternal mindful parenting was found for any of the individual decision-making measures. These findings suggest that mindful parenting supports children’s social decision-making. Future research should investigate if the combination of mindful parenting and children’s early decision-making skills predict key developmental outcomes.